Análisis de los estados financieros covid-19 y post covid-19 en las empresas hoteleras de la provincia de El Oro. - Maza Placencia, Shirley Belen; Salvador Sanchez, Genesis Carolina (Universidad Técnica de Machala, 2022)
This research is named "Analysis Of Covid-19 And Post Covid-19 Financial Statements In Hotel Companies In The Province Of El Oro", with the aim of achieving the proposed objectives, emphasising the execution of the analysis and determining the present financial situation in the companies. The methodology applied has a quantitative perspective and is under the positivist paradigm. The analytical and descriptive type of the research was implemented, the non-experimental design is applied in order not to manipulate any data provided, the deductive method will allow to observe the financial and economic effects, using observation techniques and statistical matrices managed to collect information necessary for the results. The financial analyses, the horizontal as well as the vertical ones, allowed to know the real state of the entities which were used as a sample for the elaboration of the project. At the same time, the application of financial indicators revealed that the companies' liquidity is able to cover their debts, that their income has increased, and their costs and expenses have increased, which has generated losses. The pandemic had a significant impact on hotel companies for the period 2020, losses were reflected in the exercise, but by 2021 the companies began to recover, although losses are reflected, these are controlled, gradually demonstrating the recovery of this sector.
Este trabajo se denomina “Análisis de los estados financieros covid-19 y post covid-19 en las empresas hoteleras de la provincia de El Oro.”, tiene la finalidad de alcanzar los objetivos planteados, haciendo énfasis a la ejecución del análisis y estableciendo la situación financiera presente en las empresas. La metodología utilizada tiene una perspectiva cuantitativa y está bajo el paradigma positivista, se implementó el tipo de investigación analítico y descriptivo, se aplica el diseño no experimental con el fin de no manipular ningún dato facilitado, el método deductivo permitirá observar los efectos financieros y económicos, empleando técnicas de observación y matrices estadísticas lograron recaudar información necesaria para los resultados. Los análisis financieros, tanto horizontal como vertical permitieron conocer el estado real de las entidades usadas como muestra para la elaboración del proyecto. A su vez la aplicación de indicadores financieros, da como resultado que la liquidez que tienen las empresas puede cubrir deudas, que sus ingresos aumentaron y así mismo sus costos y gastos generando pérdidas. La pandemia afectó de forma significativa a las empresas hoteleras para el periodo 2020 se reflejaron pérdidas en el ejercicio, pero para el 2021 las empresas se empezaron a recuperar, aunque se reflejan pérdidas estas son controladas, evidenciando poco a poco la recuperación de este sector.
Keywords: ESTADOS FINANCIEROS; COVID-19; HOTELERIA; ANALISIS FINANCIERO